PROSES PENYANGRAIAN BIJI KAKAO (Theobroma cacao L) PABRIK PAGERGUNUNG GLENMORE: Roasting Process of Cocoa Seeds (Theobroma Cacao L) in Pagergunung Factory at Glenmore Distric - Febri Dwi Prasetyanto, Rosiana Ulfa, Restiani Sih Harsanti (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
The roasting stage is one of the most important steps in the manufacture of cocoa powder. In the roasting process, a distinctive flavor and color are formed, besides that it will reduce the acid content in cacao, cell wall swelling is caused by protein hydrolysis and water absorption. However, the color and flavor formed still vary greatly depending on the length of the roasting process, temperature, and the tools used. The Field Work Practice (PKL) activities carried out aim to find out the cocoa processing process to become the final product. There are two types of cocoa produced at the Pagergunung factory, namely edel, and bulk types. The stages of cocoa processing carried out at the Pagergunung Factory include the stages of receiving, fermenting, drying, tempering, sorting, mixing, and packaging. One of the processes that determine the distinctive flavor and color of chocolate products is the roasting process. The roasting process carried out at the Pagergunung Glenmore Factory is carried out as much as 10 kg per roast at a temperature of 100°-120°C to make the texture of the cocoa beans more crunchy even though there is a weight loss of 1.5 kg. With this roasting method, the signature chocolate of the Glenmore Pager Mountain Factory is produced.